2015
DOI: 10.14400/jdc.2015.13.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Social relationship through SNS and adolescents' life satisfaction

Abstract: The degree of adolescents' life satisfaction is very low and the formation of social relationship through SNS is getting important to adolescents. This study aimed to examine if bridging social capital and bonding social capital through SNS and political-social participation affect the life satisfaction of adolescents. Using 2012 Adolescents Social Media Usage Survey of National Youth Policy Institute, this study analyzed 4708 data by Multiple Regression. The results showed that the life satisfaction of male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In Spain, the highest score was for the response "disagree" (28.5%) while in Portugal, the most common response was "neither agree not disagree" (28.9%). However, studies by Park and Cho (2015) have indicated that the most common activity among university nursing students is checking their social networks. Differences were found, however, with regard to staying up-to-date with social media, as a higher number of Portuguese students felt uncomfortable if they couldn't update it, whereas the majority of Spanish students indicated that they "neither agree nor disagree".…”
Section: Item X 2 Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, the highest score was for the response "disagree" (28.5%) while in Portugal, the most common response was "neither agree not disagree" (28.9%). However, studies by Park and Cho (2015) have indicated that the most common activity among university nursing students is checking their social networks. Differences were found, however, with regard to staying up-to-date with social media, as a higher number of Portuguese students felt uncomfortable if they couldn't update it, whereas the majority of Spanish students indicated that they "neither agree nor disagree".…”
Section: Item X 2 Pmentioning
confidence: 99%
“…The most common response from Portuguese students was "agree" when responding to feeling anxious when not able to check their email. Various studies have shown that this is one of the most used services by students, together with social networks (Kuss and Griffiths., 2017;Park and Cho, 2015).…”
Section: Item X 2 Pmentioning
confidence: 99%
“…Generally variables affecting Life satisfaction of youth are various, ranging from socio-demographic variables to relationships with parents and peers, learning achievement, self-esteem, and emotional problems [15]. The previous studies suggest the realm related to family and school life have the strongest influences on life satisfaction of youth [16], and especially stress related to learning is the most serious. This study has used development scale of Table 1.…”
Section: Life Satisfactionmentioning
confidence: 99%
“…Generally variables affecting Life satisfaction of youth are various, ranging from sociodemographic variables to relationships with parents and peers, learning achievement, self-esteem, and emotional problems [15]. The previous studies suggest the realm related to family and school life have the strongest influences on life satisfaction of youth [16], and especially stress related to learning is the most serious. This study has used development scale of Kim et al, (2006) to measure life satisfaction.…”
Section: Life Satisfactionmentioning
confidence: 99%